Associations between Posttraumatic Stress Symptoms, Creative Thinking, and Trait Resilience among Chinese Adolescents Exposed to the Lushan Earthquake. (17th June 2020) - Liang, Yiming; Zheng, Hao; Cheng, Jin; Zhou, Yueyue; Liu, Zhengkui
Abstract: Trauma has been shown to have a detrimental impact on individuals; however, it may also provide an opportunity for individual growth. The present study investigated the relationship between post‐traumatic stress symptoms (PTSS) and creative thinking and examined the role of trait resilience as a potential moderator of the relationship. A longitudinal study was conducted 1.5 months after the Lushan earthquake (T1: June 2013), and 102 students who experienced the earthquake were surveyed. PTSS were measured at T1 (June 2013), trait resilience was measured at T2 (October 2013), and creative thinking was measured at T3 (April 2014). PTSS and trait resilience were measured by self‐reported questionnaires, and creative thinking was assessed by the Practical Creative Thinking Test. Overall, PTSS were negatively associated with creative thinking, and trait resilience moderated this relationship. Further analysis revealed a significant positive relationship between PTSS and creative thinking for individuals with high trait resilience. The current study highlights the moderating effect of trait resilience on the relationship between PTSS and creative thinking and identifies a positive association between PTSS and creative thinking among early adolescents with high trait resilience. Our findings suggest that increased creative thinking may be a manifestation of post‐traumatic growth in the cognitive process.